2011
DOI: 10.1149/1.3583636
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Etching of Zinc Oxide for Silicon Thin Film Solar Cell Applications

Abstract: A novel approach is presented for introducing a surface morphology with beneficial light scattering properties to sputter-deposited ZnO:Al films, which are used as front contact in Si thin film photovoltaic devices. Electrochemical anodization was used to trigger local dissolution, leading to interfacial structures complementary to those commonly prepared by an etching step in diluted HCl. By systematic variation of electrochemical etching conditions and electrolytes, the essential experimental parameters for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…3. Thus, there are two competing reactions involving ZnO film dissolution, as described below [11,[16][17][18]:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3. Thus, there are two competing reactions involving ZnO film dissolution, as described below [11,[16][17][18]:…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of nanoporosity formation in ZnO films can be attributed to localized corrosion at grain boundaries, triggered by the reaction of ZnO film surface with etching agents in the electrolyte solution [11,19]. The ZnO etching behavior can be explained by the wurtzite structure and the dangling bond model, described in Ref [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides self-textured TCOs such as SnO 2 :F or ZnO:B, 13 textured contact layers are produced by a post-deposition etching step of sputter-deposited ZnO:Al. 7,14,15 To ensure an etching morphology with appropriate light scattering properties, a careful adjustment of ZnO:Al deposition parameters such as pressure, temperature, 16 film thickness, 17 and target doping concentration (TDC) 8 is needed. However, conflicting requirements in terms of ZnO:Al deposition conditions prevail since conductivity, transparency, and surface texture need to be optimized simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported the uses of various fabrication methods, such as chemical vapor deposition [11], electrochemical deposition [12], wet chemical etching [13], and electrochemical etching [14], to produce nanostructured and porous-structured ZnO. However, to the best of our knowledge, only a limited number of studies have been carried out to produce porous ZnO via [14].…”
Section: Introductionmentioning
confidence: 99%